2022
DOI: 10.1002/jmri.28219
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Apparent Diffusion Coefficients From Peritumoral Regions as Early Predictors of Response to Neoadjuvant Systemic Therapy in Triple‐Negative Breast Cancer

Abstract: Background Pathologic complete response (pCR) to neoadjuvant systemic therapy (NAST) in triple‐negative breast cancer (TNBC) is a strong predictor of patient survival. Edema in the peritumoral region (PTR) has been reported to be a negative prognostic factor in TNBC. Purpose To determine whether quantitative apparent diffusion coefficient (ADC) features from PTRs on reduced field‐of‐view (rFOV) diffusion‐weighted imaging (DWI) predict the response to NAST in TNBC. Study Type Prospective. Population/Subjects A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Park et al[18] reported that patients with PE have higher LVI levels and vascular brosis and suggested that PE is related to the tumour microenvironment. A study conducted by Musall et al[19] employing quantitative ADC measurements to assess PE characteristics and predict treatment response based on a multivariate model analysis in 108 patients with triple-negative breast cancer reported that the PE of both fat-inclusive (area under the curve [AUC] = 0.66) and fat-exclusive peritumoural regions (AUC = 0.64) could predict pCR following NST with low performance. Due to the rapid development of radiomics in recent years, there has been a considerable increase in research focusing on radiomics within peritumoural regions of breast cancer.…”
mentioning
confidence: 99%
“…Park et al[18] reported that patients with PE have higher LVI levels and vascular brosis and suggested that PE is related to the tumour microenvironment. A study conducted by Musall et al[19] employing quantitative ADC measurements to assess PE characteristics and predict treatment response based on a multivariate model analysis in 108 patients with triple-negative breast cancer reported that the PE of both fat-inclusive (area under the curve [AUC] = 0.66) and fat-exclusive peritumoural regions (AUC = 0.64) could predict pCR following NST with low performance. Due to the rapid development of radiomics in recent years, there has been a considerable increase in research focusing on radiomics within peritumoural regions of breast cancer.…”
mentioning
confidence: 99%